2011 Global Hunger Index: The Challenge of Hunger: Taming price spikes and excessive food price volatility - von Grebmer, Klaus; Torero, Máximo; Olofinbiyi, Tolulope; Fritschel, Heidi; Wiesmann, Doris; Yohannes, Yisehac; Schofield, Lilly; von Oppeln, Constanze (International Food Policy Research Institute, 2011)
The 2011 Global Hunger Index (GHI) report—the sixth in an annual series—presents a multidimensional measure of global, regional, and national hunger. It shows that although the world has made some progress in reducing hunger, the proportion of hungry people remains high. The 2011 GHI has improved by slightly more than one-quarter over the 1990 GHI, but globally, hunger remains at a level categorized as “serious.” In addition to presenting the 2011 GHI scores, the report examines the issue of price spikes and excessive food price volatility, which have significant effects on poor and hungry people.